ANALISIS PADA UMKM MEDAN MARELAN DALAM EKOSISTEM HALAL VALUE CHAIN - Nasution, Aulia Syarif; Sihotang, Mutiah Khaira (Journal of Sharia Economics, 2022)
This study aims to analyze the extent to which the application of the halal value chain chain ecosystem to the Medan Marelan MSME actors and to analyze the value chain in generating added value for the Medan Marelan MSME actors. This research was obtained on the assumption that the halal ecosystem chain can produce a value chain. This research method uses qualitative research, with the type of case study research. Data collection techniques used in this research are literature study, observation, interviews, and documentation. While the data analysis in this study used qualitative analysis according to Miles and Huberman. The data validity technique uses the triangulation method. Based on the results of research and data analysis, it is concluded that many MSME actors know about what and how the halal ecosystem is so that MSME actors in the Medan Marelan area have run the halal ecosystem well. And there are still few MSME actors who know the value chain so that a well-run halal ecosystem does not produce added value for MSME actors. This study states that the halal ecosystem can produce a value chain but it is unfortunate that many MSME actors do not know what and how the value chain is. Keywords: Halal Ecosystem; Value Chain; MSMEs